Comparison of farming income for leek and Batu 55 tangerines in Batu City - Utami, Sri; Gunawan, Cakti Indra; Santosa, Budi (Fakultas Pertanian Universitas Yudharta Pasuruan, 2024)
Introduction: Batu City is a horticultural center in East Java. One of the vegetable horticultural commodities cultivated by Batu City farmers is leeks. With the development of tangerine commodities in East Java established by the Directorate General of Horticulture in 2009 through the Program of